Studi Kelayakan Pengolahan Rumput Laut Di Desa Jang - hidayat, fizy; Citra Indah Asmarawati (LPPM Universitas Putera Batam, 2024)
Background: Indonesia is an archipelagic country with a water area of ​​6,315,222 km2 and a coastline of 99,093 km2. The underwater wealth located in the Karimun Regency area, precisely in Moro District, can be a business opportunity for small and medium enterprises (UKM). The aspects studied are Legal Aspects, Environmental Aspects, Market and Marketing Aspects, Technical and Technological Aspects, Management and Human Resources Aspects1. Market and marketing aspects owned by CV. Moro Pure Marine Collagen is able to determine demand and supply to consumers. 2. Technical and technological aspects owned by CV. Pure Marine Collagen Moro has met the eligibility criteria. 3. Human resource management aspects in Human resource management aspects in CV. Moro's Pure Marine Collagen has an organizational structure with an even distribution of duties and responsibilities in each section. 4. The legal aspect states that CV. Pure Marine Collagen Moro has a legal business entity, namely CV and has a business license such as SIU, as well as a halal certificate for collagen drink products so that this company is recognized and legal. 5. Environmental aspects examine production activities carried out by CV. Moro Pure Marine Collagen has no negative impact on the environment. Production waste is only liquid waste resulting from washing seaweed from dirt.